A brief review on recent advancement of anode materials for biogas-fed solid oxide fuel cells (SOFCs) - S Islamiyah; A Nandini (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2022)
Solid Oxide Fuel Cell (SOFC) is a fuel cell technology run at high temperatures which enable internal reforming of fuel and production of high-quality by-product heat for cogeneration. The most distinguished advantage of SOFC is its excellent fuel flexibility. Biogas is one of the alternative fuels to preferable pure hydrogen. One of the important issues in operating SOFC with biogas is the formation of carbon on anode surface. Therefore, the development of coking-resistant anode materials is essential to create a high performance and stable biogas-fed SOFC. This review provides a brief survey on the recent progress of anode materials, mainly Ni-based cermet, and the modifications to prevent carbon deposition. The current situation of biogas production and utilization in Indonesia is also briefly reviewed.